2017
DOI: 10.1007/s00520-017-3630-y
|View full text |Cite
|
Sign up to set email alerts
|

Unmet need for healthcare services in adolescents and young adults with cancer and their parent carers

Abstract: AYAs and parents had high levels of total and unmet service need, which were associated with greater emotional distress. These results highlight opportunities to re-orientate services to better meet AYA and parent needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 40 publications
2
60
0
1
Order By: Relevance
“…Additionally, AYAs' course of life might be delayed, which puts them at greater risk for poorer functioning, lower quality of life, and distress later in life . Therefore, when planning a return to school/work, these goal conflicts need to be taken into account and AYAs may need additional guidance from educational and vocational advisors within school and/or from community and government organisations around meaningful goal setting . Adolescents and young adults experience different barriers and opportunities, and, therefore, their needs are very subjective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, AYAs' course of life might be delayed, which puts them at greater risk for poorer functioning, lower quality of life, and distress later in life . Therefore, when planning a return to school/work, these goal conflicts need to be taken into account and AYAs may need additional guidance from educational and vocational advisors within school and/or from community and government organisations around meaningful goal setting . Adolescents and young adults experience different barriers and opportunities, and, therefore, their needs are very subjective.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents and young adults should be screened for educational and vocational difficulties as suggested by the psychosocial standard of care guidelines . Further access to interventions tailored to AYAs' needs and support systems such as engagement with educational advisors or promoting use of online forums/support groups for those with identified difficulties could be offered . If young cancer survivors do not successfully reintegrate into the education or employment system in early survivorship, they may experience long‐term implications in terms of earning and career potential, course of life, mental health, and social well‐being …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in the United States and Australia showed that AYAs with cancer have unmet information, service and supportive care needs [4,[6][7][8][9][10][11][12][13]. According to a systematic review conducted by Galán et al [14], the most common needs for AYA cancer survivors are "individualized information and advice", "counseling and psychological support" and " social support, and social relationship".…”
mentioning
confidence: 99%